Electroreduction of N-methylphthalimide in room temperature ionic liquids under insonated and silent conditions. - Villagrán, C; Banks, C; Pitner, W; Hardacre, C; Compton, R (2005)
The selective electroreduction N-methylphthalimide to 3-hydroxy-2-methyl-isoindolin-1-one has been performed in ionic liquids using phenol as a proton donor under silent and ultrasonic conditions. A significant increase in the rate of electroreduction is shown using ultrasonic activation and in addition high current efficiencies were observed. Some decomposition of the ionic liquid was found to have occurred under exposure to ultrasound.